TECHNOPRENEURIAL FACTORS IN THE HIGH-TECH-BASED CONSTRUCTION INDUSTRY: A STUDY OF RESIDENTIAL PROPERTY DEVELOPERS IN SURAKARTA - Ibnu Suryo; Profesor Madya Dr Juhaini Binti Jabar; TS. Dr. Nurulizwa Binti Abdul Rashid (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to identify and analyze the technopreneurial factors influencing the construction industry in Indonesia, with a focus on residential property developers. In the era of digitalization and technological advancements, the application of technopreneurship principles in the construction sector has become crucial for improving industry competitiveness and efficiency. The research methodology employed is a mixed-method approach (quantitative and qualitative), using data collection techniques such as in-depth interviews, surveys, and field observations with construction industry players, particularly residential property developers in the former Karesidenan Surakarta region. The research findings indicate that the main factors affecting technopreneurial capabilities include technological innovation, such as the use of Building Information Modeling (BIM), cloud-based project management, and the application of the Internet of Things (IoT) in property management. Additionally, the ability to adapt to digitalization, the development of technology-based human resources, and managerial and entrepreneurial capacity are key drivers. External factors such as government policies, access to technology, and digital infrastructure support also play a significant role in promoting the development of technopreneurship in this industry. In conclusion, enhancing technopreneurial capacity in the construction industry, particularly in residential property development, can be achieved through the synergy of technological innovation, workforce skills development, and policies that support technology adoption. Recommendations from this study include the need for technology-based training, strengthening collaboration between industry and educational institutions, and optimizing government policies to create a sustainable technopreneurial ecosystem.